The idea of the book in the Middle Ages : language theory, mythology, and fiction - Gellrich, Jesse M., 1942- (Cornell University Press, 2019)
This book assess the relationship of literature to various other cultural forms in the Middle Ages. Jesse M. Gellrich uses the insights ...